ENTREPRENEURIAL ORIENTATION AND SMALL AND MEDIUM ENTERPRISES GROWTH: EMPIRICAL EVIDENCE FROM SMES IN THE MANUFUCTURING SECTOR OF NAIROBI COUNTY, KENYA - Katialem, Isaac Ruto; Muhanji, Dr. Stella; Otuya, Prof. Robert (International Journal of Entrepreneurship and Project Management, 2018)
Purpose: This study sought to investigate then effect of entrepreneurial orientation on the growth of small and medium manufacturing enterprises in Nairobi County, Kenya. Methodology: The research adopted a cross section design and descriptive research approach. Stratified random sampling was used to collect primary data from 265 SMEs in the manufacturing sector from a population of 853 SMEs registered with Kenya Association of Manufacturers (KAM) in Nairobi County, Kenya. Data was collected by use of a self-administered questionnaire and analysed by statistical computations of means, percentages, and correlation and regression analysis using STATA statistical software. Findings: Findings of this research indicate that with the exception of risk taking and proactiveness; innovativeness, autonomy and competitiveness aggressiveness were all statistically significant in explaining the growth of Small and medium manufacturing enterprises in Nairobi County, Kenya. Evidence from this study supports the evidence that innovativeness, autonomy and competitiveness aggressiveness are key entrepreneurial dimensions that are imperative for enhancing SME growth. Unique contribution to theory, practice and policy: From the empirical findings we recommend that the management of SMEs need to put more emphasis on innovativeness, autonomy and competitiveness aggressiveness in order to enhance the growth of their firms